SALES INFORMATION SYSTEM DESIGN IN BUILDING SHOP USING ENTERPRISE ARCHITECTURE PLANNING METHOD - Aprilia, Windia; Ilham Fauzi, Muhammad; Yansahrita, Yansahrita (YHMM PUBLISHING, 2023)
A sales information system is a system that regulates procedures and methods for generating, analyzing, distributing, and obtaining information needed for making decisions related to sales. The Mulya Kunci Building Store experienced problems with an information system that was still manual in processing transactions, checking stock, ordering goods, and preparing reports. This study aims to help store owners and employees by introducing applications that can help them check lists and stock items, add items, create reports, manage purchasing and financial data, and manage sales transactions. This application was built using the MySQL database and the PHP programming language with the Waterfall system development method. Data collection methods used include observation, interviews, and literature studies. Context diagrams, entity relationship diagrams, and data flow diagrams are used as a system design methodology. The results showed that careful and structured needs analysis and designing a good sales information system can increase productivity and make it easier for employees to increase sales by facilitating checking of goods, processing transactions, and preparing sales reports. It can also reduce errors in each process. In the context of Mulya Kunci Building Stores, the use of a good sales information system is very important in increasing the efficiency and effectiveness of business processes.